A - Jahangir, Tahir (Oxford University Press, 2004)
The Northern Areas of Pakistan are truly magnificent in their beauty ranging from majestic mountains that kiss the sky, enchanting valleys, and fascinating terrain with forests, rivers, and glaciers. These remote areas exhibit a tranquil sense of magic with the absence of commercialization and an ethnic culture relatively unchanged by modernity. This volume presents an account as well as a guide to travelling in the Northern Areas for the inexperienced as well as the seasoned traveller. The author writes about trekking, accommodation, food, landscape and the overall travelling conditions. This is an excellent guide to the traveller on a budget of 20-30 dollars a day and is useful as a backpacker tool. The book is both a travelogue, detailing a series of journeys, as well as a guide and is essential for anyone interested in this untarnished region. Historical and social information is provided along with a key that designates precise distances and security conditions. Thirty-three photographs showing the splendour of the Karakorams and the Western Himalayas are included